RAPID-FIRE RAFIDAH Being Malaysian First - Rafidah Aziz (MPH Group Publishing Sdn Bhd, 2022)
Sometimes known as "The Iron Lady" for her forthright manner and unflinching stances on matters related to her ministerial portfolio, among others, Tan Sri Rafidah Aziz has more than made her mark on domestic politics and the world stage as Malaysia's longest-serving woman Member of Parliament and longest-serving international trade and industry minister. Now, more than a decade after retiring, she has penned this memoir, in which she reflects on her formative years, her political career and the personalities she met during her years of service, and her life in retirement. Pulling no punches, she also shares her thoughts on politics, the nation, and what Malaysians need to do to move the country forward.